(3QaY GdMLH GdeSJhQI aj eMGSf GdebUhQIs - (3ddTQja CHi GdbGSe eMeO Hf CMeO Hf eMeO GdSHJi GdZQfGWis; (3GHf MGRe GdbQWGLfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde HGdbde Chd GdbUjOI ddg eG bO gLJ jG jhe Gdfhi Ydi aDGOi f HJGQjN GdLhi s
(3BNQgG (B:s
(3jfJgi HPcQ GdHjJ hGdMeO ddg CLd ZGjI jHdZ HGdbhd dgG hjfJgi Hbhdg (B: (3hgPG BNQ TQM GdbUjOI hCbhd fjI GdeQA CHdZ ef GdYed ced s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3YdjgG JMHjS Ydi LGeY GdbQhjjf HaGS HJGQjN (B1156 (3g` s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs